A tale of sound and fury signifying everything: Argentine tango dance films as complex self-reflexive creation - Chinita, Fátima (2021)
ABSTRACT - This article equates the multidimensional artistic form of Argentine tango (dance, music and song) with the innately hybrid form of film. It compares Argentine tango culture to the height of French cinephilia in the 1950s Paris, France, arguing that they are both passionate, erotic and nostalgic ways of life. In Carlos Saura’s Tango (1998) and Sally Potter’s The Tango Lesson (1997), the intertwining of the related skills of tango practice and filmmaking are an audio-visual treat for the senses and a cognitive challenge for the mind. Their self-reflexivity promotes excess and the result is a highly expressive and complex form. They evince a cross-fertilization of reality and fiction, of art and life, typical of a perfect mise en abyme as described by Christian Metz. These films are also art musicals, although they depart from the Hollywood musical conventions. Yet, one cannot speak in their case of intermedia reflexivity, according to Petr Szczepanik’s definition, because both of them retain their qualities in a symbiotic relationship of likeness that highlights their mutual aura.